1998
DOI: 10.1038/2352
|View full text |Cite
|
Sign up to set email alerts
|

The role of metals in catalysis by the restriction endonuclease BamHI

Abstract: Type II restriction enzymes are characterized by their remarkable specificity and simplicity. They require only divalent metals (such as Mg2+ or Mn2+) as cofactors to catalyze the hydrolysis of DNA. However, most of the structural work on endonucleases has been performed in the absence of metals, leaving unanswered questions about their mechanisms of DNA cleavage. Here we report structures of the endonuclease BamHI-DNA complex, determined in the presence of Mn2+ and Ca2+, that describe the enzyme at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(196 citation statements)
references
References 36 publications
11
183
0
2
Order By: Relevance
“…This ligand arrangement allows the 2 Ca 2ϩ to come within 3.8 Å of one another without any linking atoms directly between them. The coordination chemistry of this complex is similar to that observed in nucleic acid-bound type II restriction endonucleases such as BamHI and PvuII, which require Mg 2ϩ for activity and are inhibited by Ca 2ϩ (13,14). (15) To test the importance of metal binding to complex formation, we measured the apparent affinity of whole IgG LT1009 antibody for S1P by ELISA in the presence of increasing concentrations of chelators (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This ligand arrangement allows the 2 Ca 2ϩ to come within 3.8 Å of one another without any linking atoms directly between them. The coordination chemistry of this complex is similar to that observed in nucleic acid-bound type II restriction endonucleases such as BamHI and PvuII, which require Mg 2ϩ for activity and are inhibited by Ca 2ϩ (13,14). (15) To test the importance of metal binding to complex formation, we measured the apparent affinity of whole IgG LT1009 antibody for S1P by ELISA in the presence of increasing concentrations of chelators (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peculiarity of the small subunit and nickase active centers is that all three amino acid residues are negatively charged, whereas one positively charged residue (usually lysine) is always pres ent in known restriction endonucleases. Up to the present time only one endonuclease, BamHI, is known that con tains three negatively charged residues in the active cen ter [28].…”
Section: Spatial Structures Of Subunits Of Heterodimeric Restriction mentioning
confidence: 99%
“…144 Thus, it has been proposed that a metal ion (Glu-92/Mn 2+ ) can substitute for an ammonium side chain (Lys-92) in the mechanism of EcoRV. 144 Conversely, it has been shown that Glu-77 of BamH1 is involved in metal ion binding 145 and that this residue can be substituted for a lysine without total loss of activity. 146 The activity of Glu-77/Lys mutants is enhanced in the presence of suppressor mutations that may optimize the positioning of the mutant cationic side chain.…”
Section: Electrostatic Induction By Divalent Metal Ionsmentioning
confidence: 99%
“…146 The activity of Glu-77/Lys mutants is enhanced in the presence of suppressor mutations that may optimize the positioning of the mutant cationic side chain. 147 Thus, in both studies 144,145 the term "two-metal ion mechanism" is used even though EcoRV contains only one metal ion (although replacement of the ammonium side chain of Lys-92 by Glu-92/Mn 2+ restores activity), 144 while BamH1 contains two metal ions 145 (one of which may be replaced by the ammonium side chain of Lys). 146,147 These results indicate that metal ions and positively charged amino acid side chains can be interchangeable for classes of enzyme that share a common mechanism.…”
Section: Electrostatic Induction By Divalent Metal Ionsmentioning
confidence: 99%